Conjugated porous polymers for photocatalysis: The road from catalytic mechanism, molecular structure to advanced applications. Issue 6 (November 2022) - Qiao, Shanlin; Di, Mengyu; Jiang, Jia-Xing; Han, Bao-Hang
Highlights: In this paper, the research progress of photocatalysts associated with conjugated porous polymers (CPPs) is summarized from the aspects of catalytic mechanism, molecular structure, advanced applications and outlook. The influence of various aromatic segments based organic photocatalysts are emphatically introduced. A comprehensive summary of the performance of CPPs in photocatalytic water splitting, organic transformation, degradation of pollutants, nitrogen fixation, carbon dioxide reduction and so on. Abstract: With the excessive consumption and dependence on non-renewable energy, it is urgent to seek sustainable clean energy. Using solar energy to yield target product is one of the main ways to solve environmental pollution and produce renewable resources. Conjugated porous polymers (Covalent organic frameworks, COFs. Conjugated microporous polymers, CMPs) could effectively convert solar energy into products due to their pre-designable structures and tailor-made functions. In this review, we overview the development of fundamental catalytic mechanisms, structural design principles, and summary of the advantages and progress of semi-conductive COFs/CMPs based on diverse building blocks (porphyryl-, pyrenyl-, carbazolyl-, triazinyl-, thienyl/thiazolyl-, β -ketoenamine-, conjugated alkenyl/alkynyl-, fluorenyl-), and outline the advances in COFs/CMPs as a universal platform for photocatalysts in a wide range of photocatalytic hydrogen evolution, carbon dioxide reduction, degradation of pollutions, nitrogen fixation, and organic conversion. We wish that this review will provide a comprehensive overview of photocatalysis, and boost the progress of conjugated porous polymers. Graphical abstract: Image, graphical abstract